Socio-economic inequalities in body mass index among preschool children: do sports programs in early childhood education and care centers make a difference? - Mayer, Alena; Herr, Raphael M.; Klein, Thomas; Wiedemann, Eva; Diehl, Katharina; Hoffmann, Stephanie; Blume, Miriam; Jepsen, Dennis; Sundmacher, Leonie; Andreas, Marike; Schneider, Sven (Frontiers in Public Health, 2023)
Background Overweight in childhood is considered to be one of the most serious public health challenges. Many studies have investigated individual-level determinants of children’s body mass index (BMI), yet studies exploring determinants at the meso-level are sparse. The aim of our study was to examine how a sport focus of early childhood education and care (ECEC) centres moderate the effect of parental socio-economic position (SEP) on children’s BMI. Methods We used data from the German National Educational Panel Study and included 1,891 children (955 boys and 936 girls) from 224 ECEC centres in our analysis. Linear multilevel regressions were used to estimate the main effects of family SEP and the ECEC centre sports focus, as well as their interaction, on children’s BMI. All analyses were stratified by sex and adjusted for age, migration background, number of siblings, and employment status of parents. Results Our analysis confirmed the well-known health inequalities in childhood overweight with a social gradient towards a higher BMI for children from lower SEP families. An interactive effect between family SEP and ECEC centre sports focus was found. Boys with low family SEP not attending a sport-focused ECEC centre had the highest BMI among all boys. In contrast, boys with low family SEP attending a sport-focused ECEC centre had the lowest BMI. For girls, no association regarding ECEC centre focus or interactive effects emerged. Girls with a high SEP had the lowest BMI, independent of the ECEC centre focus. Conclusion We provided evidence for the gender-specific relevance of a sport-focused ECEC centres for the prevention of overweight. Especially boys from low SEP families benefited from a sports focus, whereas for girls the family SEP was more relevant. As consequence, gender differences in determinants for BMI at different levels and their interaction should be considered in further research and preventive measures. Our research indicates that ECEC centres may decrease health inequalities by providing opportunities for physical activity.